The organic and the inner world - Doctor, Ronald M. (Ronald Manual); Lucas, Richard, 1943-2008 (Psychoanalytic ideas., 2009)
For some years, there has been an unfortunate tendency in the UK for psychiatry and psychoanalysis to be perceived as in opposition to one another, to the detriment of both disciplines. Rather than see 'organic' psychiatry on one side and 'dynamic' psychiatry on the other, the British Psychoanalytical Society now wishes to try to foster closer links between psychoanalysis and psychiatry. To this end, psychoanalysts have been going out to give presentations of their work to various psychiatric departments, in the hope of building up increasing understanding both of current developments in analy.